An EMG-based Prosthetic Hand Design and Control Through Dynamic Time Warping - TOPTAŞ, ERSİN; AKGÜN, GAZİ (My University, 2024)
Abstract – This study presents a new method to control prosthetic hands by utilizing Dynamic Time Warping (DTW) to accurately evaluate muscle contraction similarity. The objective of this research is to offer precise grip control for individuals who require prosthetic solutions. The study focuses on whether the implementation of the DTW algorithm can significantly improve the control accuracy and usability of myoelectric prosthetic hands. The initial prototypes of the prosthetic hand demonstrated promising results in achieving fundamental gripping functions through DTW-based control. The proposed prosthetic hand design points to the importance of leveraging advanced control algorithms, such as DTW, to address the specific needs of individuals requiring prosthetic solutions. By improving the prosthetic technology, the study aims to provide solutions that meet the unique challenges faced by individuals who are in need of a prosthetic hand. Keywords – Biomechatronics, Myoelectric Signals, Prosthetic Hand, Feedback Control.
Keywords: Biomechatronics; Myoelectric Signals; Prosthetic Hand; Feedback Control